Design Of a Web Based Goods Damage Recapitulation Information System - Alfianda Suci Wulansari; Murti Retnowo (Jurnal Info Sains : Informatika dan Sains, 2023)
Recapitulation of damage to goods at Madrasah Ibtidaiyah Negeri Buru still uses a manual method by utilizing Microsoft Excel as a tool. This process takes a long time and often occurs inaccurate recapitulation and loss of data. The information system for recapitulating damage to web-based goods can carry out the process of recapitulating damage to assets at Madrasah Ibtidaiyah Negeri Buru in an organized manner. The purpose of building this system is to speed up the admin work process in recapitulating damage to goods and minimizing the occurrence of unwanted things such as loss of data, repeated data (double), and data manipulation by irresponsible parties. The development model used uses a waterfall model. The method used in this research uses the prototyping method. The prototyping method contains a system design that is built using Data Flow Diagrams and Entity Relationship Diagrams. The data collection stages in this study used a process of interviews, observations, and document studies. The data used includes tables, chairs, cabinets, and whiteboards. The results of the research are in the form of an item damage recapitulation system based on determining qualifications that can be used efficiently. This system can only be accessed by the admin online. Data reports on the recapitulation of damage to goods can be downloaded with the .pdf extension.